A study on the acceptance of patients regarding self-financing of prescription medicine policy by doctors in Hospital Duchess of Kent, Sandakan / Hishamuddin Ahmad - Ahmad, Hishamuddin (2009)
Patient perception towards the introduction of self-financing of prescription medicine policy by government may vary from one individual to another. Some may accept it positively and some may not. This may due to the different background of all the patients that seeking a treatment in the public healthcare services. The main finding for this study is that government should develop a comprehensive healthcare financing mechanism that are equal to every citizens: the healthy and the affluent helps the poor who are sick, the young helps the old, the working population helps the pensioners and small families helps larger families, and collectively share the economic burden of healthcare, each according to his or her ability to do so. The paper concludes the finding in term of the acceptance of patient to the issue that might be beneficial for future research and managerial implications.